2009
DOI: 10.1002/ijc.24125
|View full text |Cite
|
Sign up to set email alerts
|

Higher regular coffee and tea consumption is associated with reduced endometrial cancer risk

Abstract: Several studies have investigated the associations between diet and endometrial cancer, but few have focused specifically on coffee and tea. In a hospital-based case-control study, we examined the associations between endometrial cancer risk and usual consumption of coffee, decaffeinated coffee, and black tea among 541 women with endometrial cancer and 541 women with an intact uterus but without a cancer diagnosis seen at Roswell Park Cancer Institute (Buffalo, New York) between 1982 and 1998. Daily frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 20 publications
4
50
0
Order By: Relevance
“…A large Swedish cohort study found a RR of 0.75 for 4 or more cups of coffee per day vs. 1 cup or less per day, using baseline intake (16). Four case-control studies (18, 3638) and two cohort studies in Norway (39) and Sweden (40) reported a non-significant inverse association, while two case-control studies in Europe (41, 42) reported a non-significant positive association.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A large Swedish cohort study found a RR of 0.75 for 4 or more cups of coffee per day vs. 1 cup or less per day, using baseline intake (16). Four case-control studies (18, 3638) and two cohort studies in Norway (39) and Sweden (40) reported a non-significant inverse association, while two case-control studies in Europe (41, 42) reported a non-significant positive association.…”
Section: Discussionmentioning
confidence: 96%
“…Only two case-control studies assessed the relationship between decaffeinated coffee and risk of endometrial cancer, and found no association (18, 41). We found a non-significant inverse association with decaffeinated coffee intake of ≥ 2 cups/d.…”
Section: Discussionmentioning
confidence: 99%
“…Tea intake and risk of endometrial cancer has been evaluated in several western populations including the US [26, 31, 32], Canada [33], and Europe [34, 35]. Although an inverse association was reported in one hospital-based case–control study [32], the remaining studies reported either positive or no associations. The combined OR for black tea and endometrial cancer was 1.20 (95% CI: 1.05, 1.38) (Table 4).…”
Section: Endometrial Cancermentioning
confidence: 99%
“… All studies Combined OR=1.20 (95% CI: 1.05, 1.38) c), d), e) Case-control studies Combined OR=1.25 (95% CI: 1.08, 1.44)c), f) a) ORs or RRs were adjusted for age [26, 31, 32, 34, 35], menstrual and/or reproductive factors [26, 31-33, 64], hormone use [26, 32, 33, 64], smoking [26, 31-33, 35], body size [26, 31-33, 64], and/or coffee intake [32, 35]. …”
Section: Tablementioning
confidence: 99%
“…However, currently known risk factors do not completely explain endometrial cancer risk. Recently, attention has focused on dietary intake in order to identify food and nutrients that might be associated with an increased or decreased risk of developing endometrial cancer [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%